Applicability of ESPGHAN Biopsy-Free Guidelines for Celiac Disease Diagnosis: Insights from Türkiye - Barış, Zeren; Canbaz, Müberra; Yılmaz, Beyzanur; Üstün, Neslihan; Aydemir, Yusuf (Turkish Journal of Gastroenterology, 2025)
Background/Aims: The biopsy-free diagnostic approach for celiac disease (CD) in children, recommended by ESPGHAN guidelines, is not widely implemented in pediatric gastroenterology centers across Türkiye. This study aimed to retrospectively evaluate patients who met ESPGHAN biopsy-free criteria but were nonetheless diagnosed through biopsy. Materials and Methods: Of 180 pediatric patients diagnosed with CD in the authors’ department over 5 years, 79 (43.8%) met the ESPGHAN biopsy-free criteria. All patients underwent routine biopsies of the duodenum, bulb, antrum, corpus, and esophagus at diag nosis. Clinical presentations, celiac serology, and endoscopic and histopathological findings were retrospectively analyzed. Results: The mean age at diagnosis was 7.48 ± 4 years (range, 2-17; M/F: 38/41). Presenting symptoms included growth failure (32.9%), abdominal pain (22.8%), constipation (8.9%), diarrhea (7.6%), anemia (6.3%), vomiting (5%), and elevated liver enzymes (1.3%). Fourteen patients (17.7%) were diagnosed via screening; 9 (64.3%) had type 1 diabetes. Endoscopy findings were consistent with CD in 77 patients; 2 had normal results. Non-celiac endoscopic findings were seen in 19 patients. Histopathology confirmed Marsh 3 lesions in 78 patients; 1 had normal findings, with tTG IgA levels normalizing at a 4-month follow-up. The positive predictive value of biopsy-free criteria was 98.7%. Non-celiac findings (in 24 patients) included Helicobacter pylori gastritis (n = 7) and eosinophilic esophagitis (n = 2). Conclusion: The biopsy-free diagnostic approach accurately identifies CD in most cases but may miss treatable conditions like eosino philic esophagitis or H. pylori infection, especially in endemic regions. Misdiagnoses, though rare, highlight the need for careful evalua tion in populations with diverse clinical presentations. Cite this article as: Barış Z, Canbaz M, Yılmaz B, Üstün N, Aydemir Y. Applicability of ESPGHAN biopsy-free guidelines for celiac disease diagnosis: insights from Türkiye. Turk J Gastroenterol. 2025;36(8):531-536.